The ABCG2 efflux transporter from rabbit placenta: Cloning and functional characterization. (February 2016) - Halwachs, Sandra; Kneuer, Carsten; Gohlsch, Katrin; Müller, Marian; Ritz, Vera; Honscha, Walther
Abstract: In human placenta, the ATP-binding cassette efflux transporter ABCG2 is highly expressed in syncytiotrophoblast cells and mediates cellular excretion of various drugs and toxins. Hence, physiological ABCG2 activity substantially contributes to the fetoprotective placenta barrier function during gestation. Developmental toxicity studies are often performed in rabbit. However, despite its toxicological relevance, there is no data so far on functional ABCG2 expression in this species. Therefore, we cloned ABCG2 from placenta tissues of chinchilla rabbit. Sequencing showed 84–86% amino acid sequence identity to the orthologues from man, rat and mouse. We transduced the rabbit ABCG2 clone (rbABCG2) in MDCKII cells and stable rbABCG2 gene and protein expression was shown by RT-PCR and Western blot analysis. The rbABCG2 efflux activity was demonstrated with the Hoechst H33342 assay using the specific ABCG2 inhibitor Ko143. We further tested the effect of established human ABCG2 (hABCG2) drug substrates including the antibiotic danofloxacin or the histamine H2 -receptor antagonist cimetidine on H33342 accumulation in MDCKII-rbABCG2 or -hABCG2 cells. Human therapeutic plasma concentrations of all tested drugs caused a comparable competitive inhibition of H33342 excretion in both ABCG2 clones. Altogether, we first showed functional expression of the ABCG2 efflux transporter in rabbit placenta. Moreover, our data suggest a similar drug substrate spectrum of the rabbit and the human ABCG2 efflux transporter. Highlights: Cloning of the ABCG2 efflux transporter from rabbit placenta (rbABCG2). Identification of the structural homology of rbABCG2 and hABCG2. Detection of the functional activity of the ABCG2 transporter in rabbit placenta. The rbABCG2 and the hABCG2 have comparable drug substrate specificity. MDCKII-rbABCG2 cells are a suitable model to study transport in rabbit placenta.